Protective role of dietary zinc on DNA damage, oxidative stress, and metal toxicity - Wong, Carmen P.; Beaver, Laura M.; Ho, Emily (Frontiers in Molecular Biosciences, 2025)
Dr. Bruce Ames illustrious career spanned many decades with far-reaching impacts both on our knowledge of DNA and in public health. In the 1990s he explored the connection between inadequate intake of micronutrients and single- and double-strand DNA breaks, genome instability due to oxidative damage, and increased susceptibility to cancer and other age-related diseases. In particular, zinc is an essential micronutrient required for many biological processes and is a key component of numerous proteins and enzymes involved in the defense against oxidative stress and DNA damage repair. Reduced zinc status due to inadequate dietary intake, reduced zinc absorption and increased excretion can lead to increased risks for infectious diseases, diabetes, cancer, and neurological disorders. Changes in zinc status can also positively or negatively modulate the outcome of exposure to toxic heavy metals including arsenic, cadmium, and lead. This mini review highlights the role of zinc in maintaining DNA integrity and antioxidant defense, the health consequences of inadequate zinc intake, and the impact of zinc status on the response to environmental exposure to toxic metals. Collectively, the work by Dr. Ames and others advances our understanding of how zinc status plays an integral role in health, and reaffirms the idea originally put forth by Dr. Ames that optimizing micronutrient intake to ensure adequate nutrition, including zinc intake, is essential in promoting health, longevity, and disease prevention.